Comparison of Sepsis in Covid 19 Infected Patients on Therapeutic Plasma Exchange Vs Tocilizumab - Hussain, Amina; Fazal, Imran; Uruj, Sana; Saleem, Asim; Sarwar, Natasha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the presence of sepsis in COVID 19 infected patients on therapeutic plasma exchange vs Tocilizumab managed at Pak Emirates Military Hospital RawalpindiStudy Design: Comparative Prospective study Place and Duration of Study: Pak Emirates Military hospital Rawalpindi, from Feb 2021 to May 2021Methodology: Patients who were diagnosed with COVID-19 on polymerase chain reaction and were oxygen dependent but not mechanical ventilation dependent were included in the study. They were randomly divided into two groups. Group I received 3-5 sessions of plasma exchange while group II received 1-2 doses of Tocilizumab. They were followed up for 10 days to look for presence of sepsis on basis of pro-calcitonin. Type of treatment used and other factors were correlated with presence of sepsis among the target population. Results: Out of 350 patients included in the study 201 (57.4%) were male while 149 (42.6%) were female. Mean age of the study participants was 49.69 ±9.456 years. 287 (82%) had procalcitonin within range and no evidence of bacterial sepsis while 63 (18%) were diagnosed as having sepsis on the basis of raised pro-calcitonin levels. Advanced age, presence of comorbidities and use of Tocilizumab had statistically significant relationship (p-value